The composition of ants (Hymenoptera: Formicidae) in Hanoi and the effect of urbanization on ant functioning groups - Thanh Van, Bui; Xuan Truong, Vu; Van Quang, Nguyen; Tuan Viet, Bui (VNU Journal of Science: Natural Sciences and Technology; Vol 33 No 2SDO - 10.25073/2588-1140/vnunst.4600, 2017)
Based on results of analyzing samples collected by the methods: on the ground bait trapping, subterranean bait trapping, direct sampling and pitfall trapping from July 2009 to December 2015 at 77 sampling plots of 21 districts in Hanoi, a total of 145 ant species belonging to 53 genera, 9 subfalilies were identified. The results of the study has added two genera (Brachymyrmex Mayr, 1868 and Formosimyrma Terayama, 2009), 42 species to Vietnam ant species composition list and added 65 species to the ant species list in Hanoi. Ant species colllected in Hanoi are classified into 9 functional groups: DD, OP, GM, CS, SC, SP, HCS, TCS and CCS. Of which, OP had the largest number of species (34 species), followed by CS (27 species), GM (26 species), SP (20 species), TCS (20 species), SC (14 species); CCS and DD groups have only one species. Opportunists-OP accounted for the highest proportion (51.7 ± 23.1%), followed by the Generalized Myrmicinae-GM (30.0 ± 21.1%), the other functional groups accounted for less than 10%. There is a statistically significant negative linear relationship between the proportion of GM and the proportion of OP in the study area. The proportion of GM tends to decrease from agricultural plots (not yet urbanized) to construction plots (being urbanized) and lowest in urban plots (urban residential plots and urban green spaces). Conversely, the proportion of OP tends to increase from agricultural plots to construction plots, and highest in urban plots. Analyzing the variation of functional groups in the urbanization in West of Hanoi shows that the degree of environmental disturbance (before, during or after construction) had a strong influence on the composition of functional groups, especially GM and OP. So we can look to the study to use ant functional groups as tools to assess the extent of human impact on the ecosystem.